Integrated crop management technology for enhanced productivity, resource-use efficiency and soil health in legumes – A review - CHOUDHARY, ANIL K; T, VARATHARAJAN; ROHULLAH, ROHULLAH; BANA, R S; POONIYA, V; DASS, A; KUMAR, ABHISHEK; N, HARISH M (The Indian Journal of Agricultural Sciences, 2020)
Under impeding production–and resource–vulnerabilities in India, our approach to agriculture needs to be redefined with inclination towards climate resilient integrated crop and resource management (ICRM) having low risk vulnerability, high factor productivity and sustained farm profitability with safe food and environmental quality. In above context, integrated crop management (ICM) practices hold great potential which take into account economic, social and environment sustainability. In irrigated agro-ecosystem of Indo-Gangetic Plains Region (IGPR), continuous cultivation of rice-wheat cropping system (RWCS) with intensive input use has caused a serious threat to agricultural sustainability with numerous production constraints. In order to diversify the IGPR production systems, pulses and other legumes like soybean and pigeonpea etc. hold great promises. Thus, legume-based cropping systems coupled with ICM practices may bring overall sustainability in IGPR. As per FAO, ICM is a recent concept in agriculture. ICM practices are the integrated technology package of appropriate site-specific crop management, integrated nutrient management, crop residue recycling, tillage management, water management, crop diversification/legume intervention, varietal selection, crop protection, energy saving and post-harvest management. Overall, this review paper highlights sufficient research findings which establish the superiority of ICM practices; in addition, it invokes for further strengthening of this research area for improving agricultural productivity, resource use efficiency and soil health with special reference to legume crops.